2020
DOI: 10.1063/5.0002297
|View full text |Cite
|
Sign up to set email alerts
|

Khovanov homology and causality in spacetimes

Abstract: We observe that Khovanov homology detects causality in (2 + 1)-dimensional globally hyperbolic spacetimes whose Cauchy surface is homeomorphic to R 2 .2010 Mathematics Subject Classification. 53C50 (Primary); 57M27, 83C75, 83C80 (Secondary).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The sky S x is homeomorphic to a circle, and viewed as a subset of the solid torus S 1 × R 2 , S x is isotopic to S 1 × {0}. For more explanation, see [CMP20] or [NT04].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sky S x is homeomorphic to a circle, and viewed as a subset of the solid torus S 1 × R 2 , S x is isotopic to S 1 × {0}. For more explanation, see [CMP20] or [NT04].…”
Section: Introductionmentioning
confidence: 99%
“…Another common link polynomial is the Alexander-Conway polynomial (also called the Conway polynomial ) ∇(L), which is categorified by link Floer homology [KS16]. Chernov, Martin, and Petkova have suggested that link Floer homology will also detect causality in this setting [CMP20]. The related knot polynomials, the Jones polynomial and the Conway polynomial, are strictly weaker link invariants than their respective categorifications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation